Regional Economic Outlook, October 2008, Middle East and Central Asia. (Regional Economic Outlook; October 2008, 2008)
Regional Economic Outlook: Middle East and Central Asia underlines that the region has continued to experience strong growth in 2008, and the short-term outlook is generally favorable. However, inflation has emerged as a key issue, and while the global credit crunch has thus far had a limited impact on regional financial markets, the financial turmoil and slowdown in developed economies could lower growth in the period ahead. Policies will need to focus on tightening the fiscal and monetary stance where appropriate, with greater exchange rate flexibility, and continuing efforts to strengthen the resilience of financial sectors.